CAREdose 4D Application in Brain CT Scan: The Effect on Dose and Image Quality - Abdolmaleki, Mohammad Sadegh; Jafari, Salman; Nikzad, Safoora (Frontiers in biomedical technologies, 2024)
Purpose: This study aimed to investigate the effect of CAREdose4D on the dose and image quality in Brain Computed Tomography (CT). Materials and Methods: Noise, Signal-to-Noise Ratio (SNR), and Contrast-to-Noise Ratio (CNR) for Gray Matter (GM), White Matter (WM), Cerebrospinal Fluid (CSF), and skull bones were investigated in brain CT scans of 60 patients. In addition, a phantom study was conducted to examine the effect of CAREdose 4D on the same subject in the brain, chest, abdomen, and pelvic CT protocols. Volume CT dose index (CTDIvol) and Dose Length Product (DLP) were recorded for each scan. Data were analyzed by T-test and Mann-Whitney statistical test with a significance level of less than 0.05. Results: The following results were obtained in active and passive modes of CAREdose 4D in brain CT of patients, respectively: CTDIvol, 15.76±3.94 and 16.96±2.14 mGy (p<0.05); DLP, 253.81±84.69 and 252.73±43.26 mGy.cm (p>0.05). There was no significant difference between SNRs and noise of various tissues of the brain (p>0.05) but CNR difference for gray matter, white matter, and cerebrospinal fluid (CSF) was significant (p<0.05). In the phantom study, SNR decreased in the active status of CAREdose 4D for the head in sequential and spiral modes, Chest, abdomen and pelvis by 7%, 84%, 45%, 20%, and 22%, respectively. Conclusion: CAREdose 4D reduces the dose without having an adverse effect on noise and SNR in brain CT scans. It is recommended newbies and untrained technicians to use CAREdose 4D.